Nurse Knowledge About Complementary Therapy Lavender Aromatherapy in Hypertension Patients at UPTD Puskesmas Tandang Buhit Balige in 2022 - Jenti Sitorus (Jurnal EduHealth, 2023)
Hypertension or often known as high blood pressure is a medical condition characterized by increased contraction of the arteries so that there is resistance to blood flow which increases blood pressure against the walls of the blood vessels, then the heart has to work harder to pump blood through the narrow blood vessels. . This study aims to examine the knowledge of nurses who use lavender aromatherapy complementary therapy in hypertensive patients. This type of research is descriptive. The research population consisted of 10 nurses at the UPTD Tandang Buhit Balige Health Center. Sampling with non-probability sampling technique, namely total sampling. Retrieval of data on nurses' knowledge about Lavender aromatherapy complementary therapy in hypertensive patients using a questionnaire sheet with direct interviews. This research resulted that the respondents who had good knowledge were 70%; 30% of respondents who have sufficient knowledge and respondents who have less knowledge do not exist. The conclusion of this study is that the knowledge of some nurses is included in the advice for the UPTD of the Tandang Buhit Balige Health Center to maintain and improve education for nurses about complementary lavender aromatherapy therapy in hypertensive patients and through seminars and trainings. 30% of respondents who have sufficient knowledge and respondents who have less knowledge do not exist. The conclusion of this study is that the knowledge of some nurses is included in the advice for the UPTD of the Tandang Buhit Balige Health Center to maintain and improve education for nurses about complementary lavender aromatherapy therapy in hypertensive patients and through seminars and trainings. 30% of respondents who have sufficient knowledge and respondents who have less knowledge do not exist. The conclusion of this study is that the knowledge of some nurses is included in the advice for the UPTD of the Tandang Buhit Balige Health Center to maintain and improve education for nurses about complementary lavender aromatherapy therapy in hypertensive patients and through seminars and trainings.